La acreditación de programas de medicina veterinaria y zootecnia en México. - Silva-Ramos, José Manuel; Martínez-Ramos, Ileana Z.; Perea-Lugo, Adriana Lucía; Bouchan-Gaeta, Adriana M.; López-Flores, Evelyn A. (Veterinaria México OA)
Introduction External evaluation and accreditation of educational programs are fundamental mechanisms for ensuring academic excellence and promoting continuous improvement in the training of professionals. In the field of Veterinary Medicine and Animal Husbandry in Mexico, the National Council for Veterinary Medicine and Animal Husbandry Education, A.C. (CONEVET), is responsible for this process, based on criteria and indicators aligned with national and international standards. CONEVET was founded on March 3, 1995, as a non-profit civil association composed of the leading professional bodies of Veterinary Medicine and Animal Husbandry in Mexico, such as the Federation of Colleges and Associations of Veterinary Zootechnicians of Mexico (FedMVZ), the National Technical Advisory Council on Animal Health (CONASA), the Mexican Association of Schools and Faculties of Veterinary Medicine and Animal Husbandry A.C. (AMEFMVZ), and the Mexican Veterinary Academy (AVM). In November 2001, it became the first accrediting body recognized by the Council for Higher Education Accreditation (COPAES) and is currently in the process of coordinating with the Higher Education Evaluation and Accreditation System (SEAES) to join the registry of External Evaluation and Accreditation Bodies (IEVA). Accreditation, promoted by CONEVET, strengthens the relevance and competitiveness of educational programs, contributes to the comprehensive training of veterinary physicians, and ensures that institutions respond effectively to the needs of the productive sector and society. Objective To demonstrate the methodology and impact of the CONEVET accreditation process on Veterinary Medicine and Animal Husbandry programs in Mexico, as a mechanism for strengthening educational quality and continuous improvement. Methodology The CONEVET accreditation process is carried out in several phases, supported by its own Reference Framework (Accreditation Manual 2022), made up of 143 quality indicators distributed into 10 categories (1. Academic Staff, 2. Students, 3. Study programs, 4. Learning Assessment, 5. Comprehensive Training, 6. Learning Support Services, 7. Liaison and Extension, 8. Research, 9. Infrastructure and Equipment, and 10. Administrative Management and Financing). Phases of the process: Institutional self assessment: The institution prepares a report with evidence that demonstrates compliance with the indicators. External evaluation: A team of peer evaluators, coordinated by the Accreditation Coordinator, carries out the visit to verify the self-assessment, review evidence and interview key actors. Recommendations and rating: The evaluation team makes observations and assigns a rating to the academic program. Collegiate opinion: The Committee of Accreditation (COACRE) analyzes the results and proposes a report, which is ratified or rectified by the CONEVET Board of Directors (CD). Results and validity: The program receive the corresponding resolution: Accredited for 5, 3, or 2 years (depending on the level of compliance) or not accredited (if it does not meet minimum quality standards). Monitoring and continuous improvement: Programs with accreditation for 3 to 5 years undergo a monitoring process. Programs accredited for 2 years or programs which opting for accreditation for the first time or subsequent accreditation may request follow-up visits or a diagnostic evaluation. Six months before the end of the validity period, the institution must begin a new evaluation process to reaffirm its accreditation. Results Accreditation Impact and Coverage. Evaluations Conducted: Since its creation, CONEVET has carried out 92 evaluation visits for accreditation purposes, resulting in 81 favorable accreditation opinions and 11 unaccredited opinions. Currently, 15 Higher Education Institutions (IES) maintain current CONEVET accreditation for their bachelor’s programs in Veterinary Medicine and Animal Husbandry. Total National Coverage: Of the 39 programs registered with the AMEFMVZ (2023), 38.5% currently have CONEVET accreditation. Nationally, there are an estimated 75 Veterinary Medicine and Animal Husbandry programs, according to data from the National Association of Universities and Higher Education Institutions (ANUIES) for the 2024-2025 academic year. 20% of bachelor’s programs in Veterinary Medicine and Animal Husbandry have been accredited to date. CONEVET recognizes as Academic Excellence programs those that have more than 5 successive accreditations with a 5-year verdict, such as: The Autonomous University of the State of Mexico - Faculty of Veterinary Medicine and Animal Husbandry and the National Autonomous University of Mexico - Faculty of Veterinary Medicine and Animal Husbandry (both with 6 accreditations). The following programs have 5 successive accreditations: Autonomous University of Nuevo León - Faculty of Veterinary Medicine and Animal Husbandry; Autonomous University of Zacatecas - Veterinary Medicine and Animal Husbandry; Autonomous University of Baja California - Institute of Veterinary Science Research; Autonomous University of Ciudad Juárez - Institute of Biomedical Sciences and University City Campus. Discussion and Conclusions The accreditation of Veterinary Medicine and Animal Husbandry programs by CONEVET has generated significant achievements, including the strengthening of teaching quality, the improvement of educational infrastructure, the standardization of evaluation criteria, and the continuous improvement of all educational processes. Among the challenges are the limited coverage of nationally accredited programs, the need to foster a culture of self-assessment, and the constant updating of indicators to respond to global and national trends in higher education, the demands of the productive sector, and current public policies. The national recognition granted by accreditation represents added value for institutions and their graduates, ensuring quality standards comparable with international accrediting bodies. Comparatively, the CONEVET model is distinguished by its specific focus on Veterinary Medicine and Animal Husbandry, which allows for a more in-depth and relevant evaluation than that of generalist organizations. In terms of conclusions, CONEVET accreditation: Contributes to the strengthening of excellent veterinary education in Mexico. It improves the comprehensive training of professionals, ensuring their academic and professional competence. It fosters connections with the productive and social sectors, promoting relevant and high-quality academic programs. It reinforces the continuous improvement of programs through monitoring processes, consolidating the credibility and prestige of accredited institutions.